Atomic and Nuclear Analytical Methods XRF, Mössbauer, XPS, NAA and Ion-Beam Spectroscopic Techniques - Verma, Hem Raj (Springer Berlin Heidelberg : Imprint: Springer, 2007)
This book is a blend of analytical methods based on the phenomenon of atomic and nuclear physics. It comprises comprehensive presentations about X-ray Fluorescence (XRF), Mössbauer Spectroscopy (MS), X-ray Photoelectron Spectroscopy (XPS), Neutron- Activation Analysis (NAA), Particle Induced X-ray Emission Analysis (PIXE), Rutherford Backscattering Analysis (RBS), Elastic Recoil Detection (ERD), Nuclear Reaction Analysis (NRA), Particle Induced Gamma-ray Emission Analysis (PIGE), and Accelerator Mass Spectrometry (AMS). These techniques are commonly applied in the fields of medicine, biology, environmental studies, archaeology or geology et al. and pursued in major international research laboratories.